Dynamic river–groundwater exchange in the presence of a saline, semi‐confined aquifer. Issue 23 (15th June 2015) - Unland, N. P.; Cartwright, I.; Daly, E.; Gilfedder, B. S.; Atkinson, A. P.
Abstract Understanding groundwater–surface water exchange in river banks is crucial for effective water management and a range of scientific disciplines. While there has been much research on bank storage, many studies assume idealized aquifer systems. This paper presents a field‐based study of the Tambo Catchment (southeast Australia) where the Tambo River interacts with both an unconfined aquifer containing relatively young and fresh groundwater (<500 μS/cm and <100 years old) and a semi‐confined artesian aquifer containing old and saline groundwater (electrical conductivity > 2500 μS/cm and >10 000 years old). Continuous groundwater elevation and electrical conductivity monitoring within the different aquifers and the river suggest that the degree of mixing between the two aquifers and the river varies significantly in response to changing hydrological conditions. Numerical modelling using MODFLOW and the solute transport package MT3DMS indicates that saline water in the river bank moves away from the river during flooding as hydraulic gradients reverse. This water then returns during flood recession as baseflow hydraulic gradients are re‐established. Modelling also indicates that the concentration of a simulated conservative groundwater solute can increase for up to ~34 days at distances of 20 and 40 m from the river in response to flood events approximately 10 m in height. For the same flood event, simulated solute concentrations within 10 m of the river increase for only ~15 days as the infiltrating low‐salinity river water drives groundwater dilution. Average groundwater fluxes to the river stretch estimated using Darcy's law were 7 m3/m/day compared with 26 and 3 m3/m/day for the same periods via mass balance using Radon (222Rn) and chloride (Cl), respectively. The study shows that by coupling numerical modelling with continuous groundwater–surface water monitoring, the transient nature of bank storage can be evaluated, leading to a better understanding of the hydrological system and better interpretation of hydrochemical data. Copyright © 2015 John Wiley & Sons, Ltd.